Prenatal Iron Deficiency and Replete Iron Status Are Associated with Adverse Birth Outcomes, but Associations Differ in Ghana and Malawi. Issue 3 (9th January 2019) - Oaks, Brietta M; Jorgensen, Josh M; Baldiviez, Lacey M; Adu-Afarwuah, Seth; Maleta, Ken; Okronipa, Harriet; Sadalaki, John; Lartey, Anna; Ashorn, Per; Ashorn, Ulla; Vosti, Stephen; Allen, Lindsay H; et al.
ABSTRACT: Background: Previous literature suggests a U-shaped relation between hemoglobin concentration and adverse birth outcomes. There is less evidence on associations between iron status and birth outcomes. Objective: Our objective was to determine the associations of maternal hemoglobin concentration and iron status with birth outcomes. Methods: We conducted a secondary data analysis of data from 2 cohorts of pregnant women receiving iron-containing nutritional supplements (20–60 mg ferrous sulfate) in Ghana ( n  = 1137) and Malawi ( n  = 1243). Hemoglobin concentration and 2 markers of iron status [zinc protoporphyrin and soluble transferrin receptor (sTfR)] were measured at ≤20 weeks and 36 weeks of gestation. We used linear and Poisson regression models and birth outcomes included preterm birth (PTB), newborn stunting, low birth weight (LBW), and small-for-gestational-age. Results: Prevalence of iron deficiency (sTfR >6.0 mg/L) at enrollment was 9% in Ghana and 20% in Malawi. In early pregnancy, iron deficiency was associated with PTB (9% compared with 17%, adjusted RR: 1.63; 95% CI: 1.14, 2.33) and stunting (15% compared with 23%, adjusted RR: 1.44; 95% CI: 1.09, 1.94) in Malawi but not Ghana, and was not associated with LBW in either country; replete iron status (sTfR <10th percentile) was associated with stunting (9% compared with 15%, adjusted RR: 1.71; 95% CI: 1.06, 2.77) in Ghana, but not PTB or LBW, and was not associated with any birth outcomes in Malawi. In late pregnancy, iron deficiency was not related to birth outcomes in either country and iron-replete status was associated with higher risk of LBW (8% compared with 16%, adjusted RR: 1.90; 95% CI: 1.17, 3.09) and stunting (6% compared with 13%, adjusted RR: 2.14; 95% CI: 1.21, 3.77) in Ghana, but was not associated with birth outcomes in Malawi. Conclusions: The associations of low or replete iron status with birth outcomes are population specific. Research to replicate and extend these findings would be beneficial. These trials were registered at clinicaltrials.gov as NCT00970866 (Ghana) and NCT01239693 (Malawi).